Fuzzy mathematical programming applied to the material requirements planning (MRP) - Arango Serna, Martín Darío; Urán Serna, Conrado Augusto; Pérez Ortega, Giovanni (Revista Técnica da Faculdade de Engenharia da de Zulia)
A rational approach toward decision-making should take into account human subjectivity, rather than employing only objective probability measures. This attitude towards the uncertainty of human behavior led to the study of a relatively new decision analysis field: Fuzzy decision making, which incorporates imprecision and subjectivity into the model formulation and solution process and represents an attractive tool to aid research in industrial engineering when the dynamics of the decision environment limit the specification of model objectives, constraints and the precise measurement of model parameters. This article gives an overview of the applications that have fuzzy logic in the industrial field and presents a MRP model to which apply some of these concepts.